PENDAMPINGAN DAN PEMASARAN HOME INDUSTRI KUE ROTI DI DESA BACU KECAMATAN TONRA KABUPATEN BONE - Nirmayanti, Nirmayanti; Permata, Srianti; Mytra, Prima (PANRITA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Home industry is a business unit/company on a small scale which is engaged in a certain industry. Usually this business only uses one two houses as production, administrasion and marketing centers at the same time. The role of the home industry is very meaningful in empowering the community to be independent in the economy. Home industry assistance is very important, especially for people who still have small businesses. Bacu village, tonra district, is a village located in the south of tonra district, bone Regency, which has never been afraid of the mentoring and marketing program for bread cakes. The purpose of this activity is so that outsiders know more about the bread cakes that are marketed. The achievement of mentoring and marketik for the home bakery industry is to market their own products both inside and outside the environment so that they can be widely applied.